1997
DOI: 10.1021/ac9611935
|View full text |Cite
|
Sign up to set email alerts
|

The Polymer-Coated SAW Sensor as a Gravimetric Sensor

Abstract: The absorption and desorption of chlorobenzene, odichlorobenzene, and chloroform in poly[n-butyl methacrylate] (PBMA) was studied in polymer-coated 104 MHz surface acoustic wave (SAW) sensors, and in freestanding polymer films by thermogravimetric analysis (TGA). The sorption processes were analyzed by a Fickian simulation and best-fit partition, and diffusion coefficients were derived. Good correlations were found between simulated and observed data. Partition coefficients derived from SAW response were indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 16 publications
(33 reference statements)
1
31
0
Order By: Relevance
“…The contribution of mass loading to the sensor response is well accepted in this field while the contribution of the viscoelastic property of polymer coating is still under investigation, even in gasphase sensors. 18,19,[25][26][27] Unfortunately, results in gas phase cannot be totally adapted or used to explain liquid-phase responses. For example, ongoing work in liquid-phase sensing has also shown that for a rubbery polymer such as PDMS viscoelasticity changes can clearly dominate sensor response.…”
Section: Mass Loading and Viscoelastic Contributions To Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of mass loading to the sensor response is well accepted in this field while the contribution of the viscoelastic property of polymer coating is still under investigation, even in gasphase sensors. 18,19,[25][26][27] Unfortunately, results in gas phase cannot be totally adapted or used to explain liquid-phase responses. For example, ongoing work in liquid-phase sensing has also shown that for a rubbery polymer such as PDMS viscoelasticity changes can clearly dominate sensor response.…”
Section: Mass Loading and Viscoelastic Contributions To Sensormentioning
confidence: 99%
“…This is consistent with reported amplification factors due to viscoelastic effects that are reported in the literature for gas-phase sensing, which are in the range of 2−4. 18,19,[25][26][27] Figure 6 Selectivity comparison of 0.64-μm PIB-coated guided SH-SAW sensor platform in the detection of toluene, xylenes, and ethylbenzene in DI water. -is the simulation result using predicted added mass loading and incremental viscoelastic changes based on experimental loss data.…”
mentioning
confidence: 99%
“…An absorption spectrum can be obtained by monitoring the intensity of reflected IR radiation and using a Beer-Lambert law expression similar to equation (4) where the path length l is replaced by an effective thickness, de, which is determined from the number of reflections and the wavelength-dependent dp [11,15]. The depth of penetration of the evanescent field is ~ 1-2 m from the surface of the prism for the wavelength range of interest in this study.…”
mentioning
confidence: 99%
“…(7) appears similar to the linear solvation energy relationship (LSER) for modeling vapor-polymer interaction under infinite dilution [3,29]. The LSER model has been widely used to explain equilibrium partition coefficients in gas-liquid chromatography (GLC), thermogravimetry (TG), and quartz crystal microbalance (QCM) and surface acoustic wave (SAW) sensing experiments [30][31][32][33][34][35]. In this model, each interaction term on the right of Eq.…”
Section: Theory Of Analyte Partitioningmentioning
confidence: 99%
“…It is always a tricky issue with materials researchers. Some representative articles and references there amply illustrate this [4][5][6][7][8][9][10][11][12][13]. The pattern recognition methods applied to SAW sensor array data has been mostly conventional ones from the statistical as well as the artificial neural network families.…”
Section: Introductionmentioning
confidence: 99%